2023
DOI: 10.1089/aut.2022.0024
|View full text |Cite
|
Sign up to set email alerts
|

“It Is a Big Spider Web of Things”: Sensory Experiences of Autistic Adults in Public Spaces

Abstract: Background: Sensory processing differences are commonly experienced by autistic individuals, and some sensory experiences can greatly impact the mental health and quality of life of individuals.Previous research suggests that adapting the sensory nature of environments may improve individual experiences and engagement with these spaces. However, knowledge about which public places are particularly disabling is limited, especially from the perspective of autistic individuals. Little is also known about what in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 49 publications
1
23
1
Order By: Relevance
“…However, the authors’ discussion of the varied (and sometimes contradictory) stimuli that can be distressing for autistic adults highlights the heterogeneity of autistic peoples’ experiences with sensory stimuli. In a subsequent study, MacLennan, Woolley et al (2022) noted that outdoor spaces were among the most enabling sensory spaces, according to autistic participants. Natural stimuli may therefore serve a calming or beneficial purpose for some (but not all) autistic people.…”
Section: Introduction and Literature Reviewmentioning
confidence: 95%
“…However, the authors’ discussion of the varied (and sometimes contradictory) stimuli that can be distressing for autistic adults highlights the heterogeneity of autistic peoples’ experiences with sensory stimuli. In a subsequent study, MacLennan, Woolley et al (2022) noted that outdoor spaces were among the most enabling sensory spaces, according to autistic participants. Natural stimuli may therefore serve a calming or beneficial purpose for some (but not all) autistic people.…”
Section: Introduction and Literature Reviewmentioning
confidence: 95%
“…By contrast, the neurodiversity perspective holds that when there are decreases in quality of life associated with being autistic, they are primarily caused by an interaction between the autistic person and their environment (Chapman, 2019). For example, sensory sensitives to light or sound can make it more challenging for autistic people to navigate physical environments designed for neurotypical people (Belek, 2019;MacLennan et al, 2022). Likewise, the stigmatization of nonneurotypical behavior (e.g., hand-flapping) can make it difficult for autistic individuals to navigate common social contexts (Rothman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified that there are multiple factors that need to be considered when making spaces more enabling for autistic people, and these go far beyond just reducing sensory input (Doherty et al, 2023; Garner et al, 2022; MacLennan et al, 2022; Stogiannos et al, 2022). MacLennan et al (2022) identified six principles determining how disabling or enabling sensory environments are, which include (1) the ‘Sensoryscape’ (i.e. the intensity and nature of sensory input), (2) Space constraints, (3) Predictability, (4) Understanding from others, (5) Adjustments, and (6) Opportunity for Recovery (see Figure 1).…”
mentioning
confidence: 99%
“…Meanwhile, in relation to the ‘Understanding’ theme, the NDTI (2020) recognised the need to increase the understanding of staff in in-patient settings, and Clonakilty’s ‘autism-friendly’ town status required staff training across services, schools and businesses. However, the research by MacLennan et al (2022) exposed that some adjustments are not fit-for-purpose. For example, some autistic people said that quiet hours at supermarkets are unsuitable as they are infrequent and at inconvenient times, and that the Sunflower Lanyard scheme was often misunderstood and not effective in getting autistic people the support they need.…”
mentioning
confidence: 99%
See 1 more Smart Citation